A defined anthocyanin mixture sourced from bilberry and black currant inhibits Measles virus and various herpesviruses - Rinu Sivarajan; Heike Oberwinkler; Valeria Roll; Eva-Maria König; Maria Steinke; Jochen Bodem (BMC, 2022)
Abstract Background Anthocyanin-containing plant extracts and carotenoids, such as astaxanthin, have been well-known for their antiviral and anti-inflammatory activity, respectively. We hypothesised that a mixture of Ribes nigrum L. (Grossulariaceae) (common name black currant (BC)) and Vaccinium myrtillus L. (Ericaceae) (common name bilberry (BL)) extracts (BC/BL) with standardised anthocyanin content as well as single plant extracts interfered with the replication of Measles virus and Herpesviruses in vitro. Methods We treated cell cultures with BC/BL or defined single plant extracts, purified anthocyanins and astaxanthin in different concentrations and subsequently infected the cultures with the Measles virus (wild-type or vaccine strain Edmonston), Herpesvirus 1 or 8, or murine Cytomegalovirus. Then, we analysed the number of infected cells and viral infectivity and compared the data to non-treated controls. Results The BC/BL extract inhibited wild-type Measles virus replication, syncytia formation and cell-to-cell spread. This suppression was dependent on the wild-type virus-receptor-interaction since the Measles vaccine strain was unaffected by BC/BL treatment. Furthermore, the evidence was provided that the delphinidin-3-rutinoside chloride, a component of BC/BL, and purified astaxanthin, were effective anti-Measles virus compounds. Human Herpesvirus 1 and murine Cytomegalovirus replication was inhibited by BC/BL, single bilberry or black currant extracts, and the BC/BL component delphinidin-3-glucoside chloride. Additionally, we observed that BC/BL seemed to act synergistically with aciclovir. Moreover, BC/BL, the single bilberry and black currant extracts, and the BC/BL components delphinidin-3-glucoside chloride, cyanidin-3-glucoside, delphinidin-3-rutinoside chloride, and petunidin-3-galactoside inhibited human Herpesvirus 8 replication. Conclusions Our data indicate that Measles viruses and Herpesviruses are differentially susceptible to a specific BC/BL mixture, single plant extracts, purified anthocyanins and astaxanthin. These compounds might be used in the prevention of viral diseases and in addition to direct-acting antivirals, such as aciclovir.